Case report of cardiogenic shock in COVID-19 myocarditis: peculiarities on diagnosis, histology, and treatment. Issue 10 (9th September 2021) - Fiore, Giorgio; Sanvito, Francesca; Fragasso, Gabriele; Spoladore, Roberto
Abstract: Background: The year 2020 was dramatically characterized by SARS-CoV-2 pandemic outbreak. COVID-19-related heart diseases and myocarditis have been reported. Case summary: A 45-year-old healthy male was admitted to the intensive care unit of our hospital because of cardiogenic shock. A diagnosis of COVID-19 infection and myocarditis was done. We present here several peculiarities about diagnostic workup, myocardial histological findings, choice of treatment, and the patient clinical course at 3 and 8 months of follow-up. Discussion: COVID-19 myocardial damage and myocarditis are mainly linked to the cytokine storm with mild myocardial inflammatory infiltrate and very unusual platelet microclots in the setting of the microvascular obstructive thrombo-inflammatory syndrome. Counteracting the inflammatory burden with an interleukine-1 inhibitor appeared safe and led to a dramatic and stable improvement of cardiac function.